Anti-leishmanial activity of Brevinin 2R and its Lauric acid conjugate type against L. major: In vitro mechanism of actions and in vivo treatment potentials - Zahedifard, Farnaz; Lee, Hyeryon; No, Joo Hwan; Salimi, Mona; Seyed, Negar; Asoodeh, Ahmad; Rafati, Sima (PLOS Neglected Tropical Diseases, 2019)
Author summary Seeking novel drugs against leishmaniasis is a necessity due to inefficiency of current medications. Brevinin 2R, as a non-hemolytic natural antimicrobial peptide, was effective against vast majority of bacterial and fungal infections as well as cancerous cell lines. In this regard in the current study, the efficacy of Brevinin 2R and its lauric acid conjugate version were studied against L. major parasite growth inhibition at in vitro and in animal model. The results exhibited that, conjugation of fatty acid to Brevinin 2R exacerbated anti-leishmanial effect. L- Brevinin 2R resolved the promastigotes through membrane disruption and changes in the membrane and mitochondrial potential. Also, L- Brevinin 2R was able to limit successfully the parasite load in the lymph nodes of L. major infected animals.